PROBLEMS FACED BY ENGLISH DEPARTMENT STUDENTS IN CRITICAL READING - Rahmi, Gita (UG Journal, 2020)
This research was conducted to find out problems faced by students in critical reading because based on preliminary research, it was found that the students had problems in reading. For that reason, this research used descriptive method to analyze the problems faced by students in critical reading. Population of the research was English department students of a university in Padang. Cluster sampling technique was used to choose sample. The sample was a class that consisted of 34 students. Data were taken by using test and interview. Try Out was also conducted before taking data. The result of test showed that the scores of students in the sub skills of critical reading were poor in average. From all students tested, none got scores in the range of 66-100. In contrast, 50.00 % of the students got score in the range of 41-55 (D), 35.29 % of them had score in the range of 0-40 (E), and there were only 14.70% students got score in the range of 56-65 (C). Then, based on interview done, the students admitted that they had problems in answering questions related to critical reading especially to the subskills tested, writer’s purpose, writer’s tone, and writer’s point of view. The problems were vocabulary, background knowledge, complex sentences, knowledge of the skills, knowledge of strategies to know the skills, and others. Based on explanation above, it can be concluded that students’ critical reading ability is still poor and based on the interview, they had problems in critical reading. For that condition, it is suggested to English Department to revise the syllabus for teaching Reading Class. The lecturers are also hoped to give extra exercise and assignment related to critical reading to the students to make them become accustomed to reading.